Factors limiting the adoption of mobile board games as a tool for promoting gamification A quantitative analysis - Randle, O. A.; Oni, A. A. (South African Journal of Higher Education, 2025)
Awale, also known as Mancala, is a popular board game, which has received most digital implementations of the game, which competes with Myriad Software’s Mancala, have been studied extensively by various academics. Computer scientists and programmers have used various machine learning techniques to experiment with this ability. Literature shows that artificial intelligence has been used successfully to mimic play and compete against human strategies and techniques. However, African board games have the ability to be underutilised as a medium to support the learning abilities of young children. This has greatly reduced the ability of gamification to assist in improving the learning abilities of children in African schools. The article aims to identify the factors that prevent gamification in Public Universities. The article uses the unified theory of acceptance and use of technology as its theoretical framework. This theory focuses on the adoption of technology and the factors that limit its adoption. Furthermore, the article employs a positivist approach. The results of the research identified significant relationship between Social influence, facilitating conditions, hedonic motivation, price value, habit and behavioural intention while non-significant relationship were identified between performance expectancy, effort expectancy towards behavioural intention. The importance of these results is they can guide stakeholders in understanding the key factors which influence adoption of mobile board games as tools for learning.